Evaluating the Reliability of Glass Ionomer Cements in Restorative Dentistry for Primary Teeth: A Systematic Review - selsebil laajimi; souha Saidi; farah chouchene; yamina elelmi; ahlem Baaziz (International Journal of Advanced Health Science and Technology, 2026)
The clinical reliability of glass ionomer cements (GICs) in pediatric restorative dentistry remains a critical concern due to variations in material formulations and their performance in primary teeth. Despite continuous advancements, inconsistencies in clinical outcomes and influencing factors necessitate a comprehensive evaluation of current evidence. This systematic review aimed to assess and compare the clinical performance of different types of GICs used in restorations of primary teeth and to identify the factors affecting their success rates. A systematic search was conducted across four electronic databases MEDLINE, Cochrane Central, ScienceDirect, and EBSCOhost covering studies published between 2013 and 2025. The review followed PRISMA guidelines and applied the PICO framework to define eligibility criteria. Only randomized controlled trials involving pediatric patients with vital primary teeth were included. Study quality was assessed using the Modified Jadad Scale, and due to heterogeneity in methodologies, a narrative synthesis approach was adopted. Out of 237 identified records, seven studies met the inclusion criteria. The findings demonstrated that resin-modified glass ionomer cements (RMGICs) and high-viscosity glass ionomer cements (HVGICs) exhibited superior clinical success rates, reaching approximately 94% and 77%, respectively. These materials showed favorable longevity, enhanced marginal integrity, and satisfactory esthetic outcomes. Key factors influencing restoration success included the type of molar restored (p = 0.003) and the affected surface (p < 0.001), while patient-related variables showed no significant association. In conclusion, RMGICs and HVGICs are currently the most reliable restorative materials for primary teeth due to their improved mechanical and bioactive properties. However, restoration success is multifactorial, depending not only on material selection but also on clinical technique and cavity characteristics. Future research should focus on long-term, standardized clinical trials to strengthen evidence-based recommendations.